(untitled) (Czech Journal of International Relations, 2001)
Petr Jehlička, Jiří Tomeš, Petr Daněk /editoři/: Stát, prostor , politika. 1. vydání. Praha: Univerzita Karlova; Brno: Masarykova univerzita, 2000, 274 stran, ISBN 80-238-5566-2.